DESAIN PROTOTIPE MEDIA PEMBELAJARAN SIMULASI SISTEM REM MOBIL UNTUK PEMBELAJARAN SISWA SMK JURUSAN OTOMOTIF - Ardiyanta, Anggara Sukma (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2017)
This research using research and development method to develop learning media based on simulation. The researcher develops Braking System learning media using Blender 3D and Unity 3D. The result of this research is prototype of braking system application in 3D animation form. This media hopefully can help student in order to understanding how braking system works and its component.